Development of a detection block of a combined mode scintillator-photodiode system (counting-current) for azimuthal detecting complexes - Nekrasov, V.V.; Belogub, V.V.; Selegenev, E.M.; Grynyov, B.V.; Borodenko, Yu.A. (Functional Materials, 2004)
A small-sized gamma-detection block of scintillator-photodiodetem is reported. The block operates in the 0.05-3.0 meV energy range and the dose rate range from 10⁻⁶ to 10³ R/h and more. The detection block operates in a combined counting-current mode with spectrometry functions. Transition from the counting mode to the current mode and back is carried out automatically. The detection block is designed for use in azimuthal detectin g complexes of surveyor robots, in multifunctional dosimeters, direction-finding dosimeters, etc.